2021
DOI: 10.3390/md19110608
|View full text |Cite
|
Sign up to set email alerts
|

Marine Sulfated Polysaccharides: Preventive and Therapeutic Effects on Metabolic Syndrome: A Review

Abstract: Metabolic syndrome is the pathological basis of cardiovascular and cerebrovascular diseases and type 2 diabetes. With the prevalence of modern lifestyles, the incidence of metabolic syndrome has risen rapidly. In recent years, marine sulfate polysaccharides (MSPs) have shown positive effects in the prevention and treatment of metabolic syndrome, and they mainly come from seaweeds and marine animals. MSPs are rich in sulfate and have stronger biological activity compared with terrestrial polysaccharides. MSPs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 102 publications
1
14
0
Order By: Relevance
“…Xanthophylls were the most prevalent pigments in species AN, FS, LS, PC and UP (Table 1), fucoxanthin being the compound with the highest concentration, specifically in the ethanolic extracts of LS and the chloroform extracts of UP ranging ~3.9 mg•g −1 dw. There is wide evidence reporting that fucoxanthin is the most abundant pigment in brown algae [16], which supports the experimental results obtained. Indeed, fucoxanthin is the only pigment present in all extracts from all species, agreeing with the previous literature that admits this pigment as characteristic of brown algae [19].…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Xanthophylls were the most prevalent pigments in species AN, FS, LS, PC and UP (Table 1), fucoxanthin being the compound with the highest concentration, specifically in the ethanolic extracts of LS and the chloroform extracts of UP ranging ~3.9 mg•g −1 dw. There is wide evidence reporting that fucoxanthin is the most abundant pigment in brown algae [16], which supports the experimental results obtained. Indeed, fucoxanthin is the only pigment present in all extracts from all species, agreeing with the previous literature that admits this pigment as characteristic of brown algae [19].…”
Section: Resultssupporting
confidence: 86%
“…With the aim of comparing our results with those by other authors, Table 2 includes the pigments previously extracted from these algae, using different extraction solvents and determination In addition to chlorophylls, carotenoids are also found in the extracts of brown algae to a greater extent, being represented by xanthophylls and, secondarily, by carotenes. This prevalence of xanthophylls is a characteristic feature of brown algae, which are responsible not only for their coloration but also for most of their biological activities, together with polysaccharides [15][16][17]22]. A total of seven carotenoids, six xanthophylls (compounds X1-X6) and one carotene (compound B1) were reported in brown algae extracts (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polysaccharides have a variety of biological and pharmacological activities, especially in treating diseases, which have been summarized in several recent reviews. For example, polysaccharides have been reported to play protective roles in metabolic syndrome, cardiovascular diseases, and neurodegenerative diseases due to their activities in glucose and lipid metabolism regulation and antioxidant and anti-inflammation activities [ 8 , 9 , 10 , 11 , 12 ]. Other studies revealed algal polysaccharides killing tumor cells via apoptosis while reducing the adverse effect of chemotherapy [ 13 ].…”
Section: Overview Of Liver Diseases and Polysaccharidesmentioning
confidence: 99%